Antimicrobial Resistance An Open Challenge - Cristina Ossiprandi, Maria (IntechOpen, 2015)
Antibiotic resistance has become a worldwide health issue, globally recognized as the first priority by WHO. Many forms of resistance can spread with remarkable speed and cross international boundaries. World health leaders are devoting efforts to the problem by planning strategies for monitoring the effectiveness of public health interventions and detecting new trends and threats. This volume focuses on the problem from different perspectives, taking into consideration geographical dissemination (soil and water), human medicine (methicillin-resistant Staphylococcus aureus and Klebsiella pneumoniae) and veterinary (Enterococcus spp.) impact and molecular analysis. The purpose of this volume is to provide a useful tool for control and prevention and to discuss useful epidemiological data concerning ways of obtaining an accurate picture of resistance in different communities.